2010
DOI: 10.1111/j.1469-8749.2010.03710.x
|View full text |Cite|
|
Sign up to set email alerts
|

Plasticity of the visual system after early brain damage

Abstract: The aim of this review is to discuss the existing evidence supporting different processes of visual brain plasticity after early damage, as opposed to damage that occurs during adulthood. There is initial evidence that some of the neuroplastic mechanisms adopted by the brain after early damage to the visual system are unavailable at a later stage. These are, for example, the ability to differentiate functional tissue within a larger dysplastic cortex during its formation, or to develop new thalamo-cortical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 126 publications
(234 reference statements)
5
58
1
2
Order By: Relevance
“…We would speculate that from early gestation, the trajectories of the optic radiations in the affected hemisphere may deviate from their normal course, bypass the AVMs, and reach their final target in the occipital lobe. A similar process can be observed in the visual system of patients with unilateral peri-ventricular brain damage early in the third trimester of gestation [9]. Our speculation is also consistent with animal studies [13,20,21] and postmortem findings in human fetuses [10] which showed that developing geniculo-striate axons after mid-gestation "wait" in the subplate for weeks before entering the cortical plate.…”
Section: Risk Factors Of Preexisting Vfdssupporting
confidence: 90%
See 1 more Smart Citation
“…We would speculate that from early gestation, the trajectories of the optic radiations in the affected hemisphere may deviate from their normal course, bypass the AVMs, and reach their final target in the occipital lobe. A similar process can be observed in the visual system of patients with unilateral peri-ventricular brain damage early in the third trimester of gestation [9]. Our speculation is also consistent with animal studies [13,20,21] and postmortem findings in human fetuses [10] which showed that developing geniculo-striate axons after mid-gestation "wait" in the subplate for weeks before entering the cortical plate.…”
Section: Risk Factors Of Preexisting Vfdssupporting
confidence: 90%
“…We can also conclude that as a congenital disease, many AVMs might have coexisted with the optic radiation and visual cortex from very early phases of development and the visual pathway may modify continuously by virtue of brain plasticity to maintain normal VFs. This can also be observed from the findings of Guzzeta et al One patient in their study showed normal VFs despite a large lesion of the left peri-ventricular white matter involving most of the tissue where optic radiations would normally sit [9]. Most occipital AVMs may present with normal VFs unless a hemorrhage occurs.…”
Section: Coexistence Of Occipital Avms and Optic Pathwaysupporting
confidence: 61%
“…Some case reports show diffusion tensor tractograms of thalamocortical connections that are displaced by lesions but still reach cortical areas in individuals with early acquired brain lesions (eg, Staudt et al 30 ; Guzzetta et al 31 ). With our method, we observed, in several cases and in all lesion types, that both the CST and TRS1 on the lesion side have altered paths when passing lesion-affected areas.…”
Section: Fiber-tracking Methodsmentioning
confidence: 99%
“…Indeed, clinical editorials have highlighted that the relationship between observed clinical manifestations and the extent of brain damage in CVI is complex and not yet fully understood (Guzzetta et al, 2010). Additionally, attention has been called to the value of advanced neuroimaging techniques in helping to better understand the relationship between brain maldevelopment and visual impairment in CVI (Good, 2001; Edmond and Foroozan, 2006; Murakami et al, 2008).…”
Section: Introductionmentioning
confidence: 99%